2021
DOI: 10.3390/ijerph18063141
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Fitness Program in the School Setting during the COVID 19 Pandemic: Effects of an 8-Week CrossFit Program on Psychophysical Well-Being in Healthy Adolescents

Abstract: Background: The Italian government promoted social distancing, in which the suspension of any social event, suspension of all activities practiced in gyms, sports centers and their closure was ordered. The social distancing in the school environment and the use of strategies to limit viral infection are not very compatible with group motor activity and team sports. The aim of this study is to verify the effectiveness of a CrossFit program in order to mitigate the deficits in fitness caused by COVID-19 preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 46 publications
1
25
1
1
Order By: Relevance
“…These results are also consistent with emerging literature on the role of physical activity in mental health in the context of the COVID-19 pandemic. A study found that implementing fitness programs among adolescents during COVID-19 lockdowns in Italy increased Regulatory Emotional Self-Efficacy scores after 8 weeks [45], and a qualitative study highlighted the role of physical activities and social connections in student-athletes' mental health [46]. However, schools around the world continue to face many challenges to promote physical activities and physical education in the context of COVID-19 [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…These results are also consistent with emerging literature on the role of physical activity in mental health in the context of the COVID-19 pandemic. A study found that implementing fitness programs among adolescents during COVID-19 lockdowns in Italy increased Regulatory Emotional Self-Efficacy scores after 8 weeks [45], and a qualitative study highlighted the role of physical activities and social connections in student-athletes' mental health [46]. However, schools around the world continue to face many challenges to promote physical activities and physical education in the context of COVID-19 [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research also suggest the need for gymnastics to rethink training programs [34,35], making them more suitable in terms of athletic loads so as to prevent the development of musculoskeletal pain syndromes, in particular those of chronic nature [36,37]. To achieve this, it is desirable to integrate traditional training programs with new technologies, which are increasingly widespread in kinesiology and sports rehabilitation, with therapeutic and preventive purposes [38][39][40][41][42][43][44][45]. These are already used in other areas of rehabilitation, such as neurological rehabilitation [46], in which the new frontiers of telemedicine even provide the possibility of using serious games based on virtual reality for rehabilitative purposes and in order to follow and treat patients remotely [47].…”
Section: Discussionmentioning
confidence: 99%
“…There are not many studies that present implemented programs during the covid-19 pandemic crisis and the return of children to school after Lockdown [30], [31], [32], [33], [34], [35]. The aforementioned studies present educational interventions in the crisis and in the return to school after Lockdown and aim at mental resilience [26].…”
Section: Re-entry To School During the Pandemic Covid-19 And Psychosocial Interventionsmentioning
confidence: 99%